Kosmopolitanisme Vernakular: Respon Indonesia terhadap Konflik Rohingya di Myanmar - Susanti, Endang; Hamdani, Hamdani (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2024)
The Rohingya conflict in Myanmar is one of the conflicts that has attracted global attention and triggered responses from various countries, including Indonesia. As a country with the largest Muslim population and a high commitment to humanitarian principles, Indonesia has a strategic position in responding to the Rohingya conflict in Myanmar. This study aims to analyze vernacular cosmopolitanism in understanding the reality of the conflict that occurred in Southeast Asia, especially in how Indonesia responded to the Rohingya ethnic conflict in Myanmar. This study uses qualitative methods with literature analysis and case studies to analyze how vernacular cosmopolitanism, which includes universal Islamic values, can be interpreted locally to ground peace, tolerance, and justice in resolving complex conflicts. This study uses the concept of vernacular cosmopolitanism from Pnina Werbner to analyze Indonesia's response to the Rohingya conflict in Myanmar. This study produces the fact that the concept of vernacular cosmopolitanism is practiced by Indonesia in responding to the Rohingya conflict in Myanmar. The values of openness, tolerance and responsibility towards fellow human beings are manifested in the provision of humanitarian assistance and acceptance of Rohingya refugees. In addition, Indonesia also acts as a mediator and facilitator in resolving conflicts using regional diplomacy based on consensus. Indonesia also uses religious diplomacy by facilitating interfaith dialogue to promote tolerance and peace. All that Indonesia does is solely out of concern for fellow human beings and to realize world peace.